2018
DOI: 10.1071/an15739
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quantity and source of rumen nitrogen on the efficiency of microbial protein synthesis in steers consuming tropical forage

Abstract: Low values for the efficiency of microbial protein synthesis (EMPS) in cattle consuming tropical forages are related to low rumen degradable crude protein (RDP) intakes. This study examined the effect on the EMPS of the quantity and source of nitrogen (N) supplied to the rumen of eight entire and four rumen-fistulated Brahman steers consuming mature tropical grass hay (57.3 g crude protein/kg DM). Four treatment diets were fed in a Latin square design and included a basal diet of mature pangola grass (Digitari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…The rumen volumes estimated here have potentially large errors given the non-steady state conditions under which the CrEDTA marker is used but nevertheless they provide a comparative relative estimate. The values are comparable to the values derived by Poppi et al (1981a) under steady state conditions and Bowen et al, (2017) under grazing conditions using a similar procedure. Visual observations, obtained when the cannula was opened for sampling, indicated that the rumens were quite full except for the dry season speargrass, which was also seen in the estimate by marker dilution.…”
Section: Accepted Manuscriptsupporting
confidence: 83%
See 4 more Smart Citations
“…The rumen volumes estimated here have potentially large errors given the non-steady state conditions under which the CrEDTA marker is used but nevertheless they provide a comparative relative estimate. The values are comparable to the values derived by Poppi et al (1981a) under steady state conditions and Bowen et al, (2017) under grazing conditions using a similar procedure. Visual observations, obtained when the cannula was opened for sampling, indicated that the rumens were quite full except for the dry season speargrass, which was also seen in the estimate by marker dilution.…”
Section: Accepted Manuscriptsupporting
confidence: 83%
“…Insert Table 7 with ryegrass (10.8 h) (Bowen et al, 2017). The important parameter is the actual RTs, which are lower than those suggested from pen studies with tropical grass hays (16-19 h) (Poppi et al, 1981a).…”
Section: Rumen Parametersmentioning
confidence: 96%
See 3 more Smart Citations